The Implementation of the Realistic Mathematics Education (RME) Model and Its Effect on the Mathematics Learning Outcomes of Phase F MPLB Students at SMKN 2 Padang - Adela Sukma Putri; Teni Suriani; Dina Novarina Perdana (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study was motivated by the low mathematics learning outcomes of Phase F students in the Office Management and Business Services program at SMKN 2 Padang. This study aimed to determine whether the mathematics learning outcomes of students taught using the Realistic Mathematics Education (RME) model were better than those of students taught using conventional learning among Phase F MPLB students at SMKN 2 Padang.This research used a quasi experimental method with a randomized control group only posttest design. The population consisted of all Phase F MPLB students at SMKN 2 Padang in the 2025/2026 academic year. The sample was selected through random sampling after normality and homogeneity tests were conducted. The experimental class was taught using the RME model, while the control class was taught using conventional learning.Data were collected through a posttest and analyzed statistically. The Liliefors test showed that both data groups were normally distributed, with L_count for MPLB 2 = 0.143 < L_table = 0.161 and Lcount for MPLB 3 = 0.122 < L_table = 0.157. The Bartlett test showed that both groups were homogeneous, with χ²_count = 1.328 < χ²_table = 3.481. Hypothesis testing using the independent sample t-test obtained t_count = 3.91 > t_table = 1.67 at α = 0.05 with df = 59. Therefore, H₀ was rejected and H₁ was accepted.Thus, it can be concluded that the mathematics learning outcomes of students taught using the RME model were significantly better than those of students taught using conventional learning.